An easy direct arylation of 5-pyrazolones - Gong, Hao; Yang, Yiwen; Wang, Zechao; Kuang, Chunxiang (Beilstein Journal of Organic Chemistry, 2013)
A mild, efficient and catalytic ligand-free method for the direct arylation of 5-pyrazolones by Pd-catalyzed C–H bond activation is reported. The process smoothly proceeds and yields are moderate to excellent.
Keywords: arylation; aryl halide; C–H bond activation; Pd(OAc)2; pyrazolone